On the Correct Solvability of One Cauchy Problem - Litovchenko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish a criterion for convolutors in certain S-type spaces. Using this criterion, we prove the correct solvability (in both directions) of one Cauchy problem in these spaces.